Koncepcja artysty i konflikt pokoleniowy w "Liście do Pizonów" Horacego. Glosa do antycznej krytyki literackiej - Kopek, Wojciech (Colloquia Litteraria, 2018)
This paper, taking as a starting point Horace’s “Epistle to the Pissos”, its form and structure, approaches the Horatian problem of an artist involved in the Roman social issues, dominated by such categories as pietas and dignitas, both in relationship to the poet himself and to the social position and role of the profession of an artist (dichotomy: otium – negotium). Moreover, the role of a literary critic is discussed. A literary critic, by imposing certain rules and constraints on the artist, himself is not free of the social pressure being the result of the client/patron dependence. Writing in this context becomes an art of a compromise of values, between social and legal solutions founded in Rome’s traditional ‘community of citizens’ and the aesthetic limits and needs of the new generation of creators and their audiences.